Solubility measurement and thermodynamic modeling of solid-liquid equilibria in quaternary system NaCl–CaCl2–SrCl2–H2O at 323.15 K. (September 2019) - Yang, Lan; Li, Dan; Li, Yupeng; Meng, Lingzong; Deng, Tianlong; Guo, Yafei
Graphical abstract: Highlights: The phase diagrams in systems NaCl–SrCl2 –H2 O and NaCl–CaCl2 –SrCl2 –H2 O were presented. The Pitzer thermodynamic model of the two systems was constructed. The calculated solubility data agree well with the experimental values. Abstract: The solid-liquid phase equilibria in the systems NaCl–SrCl2 –H2 O and NaCl–CaCl2 –SrCl2 –H2 O at 323.15 K were studied with the isothermal dissolution method. The solid-liquid equilibrium phase diagrams were constructed with the experimental results. A comparison of the diagrams of system NaCl–SrCl2 –H2 O from 288.15 to 373.15 K shows that area of strontium chloride salt region decreased obviously whereas the areas of NaCl almost invariant. The dry-salt diagram of the NaCl–CaCl2 –SrCl2 –H2 O system consists of four single-salt crystallization regions for NaCl, SrCl2 ·6H2 O, SrCl2 ·2H2 O and CaCl2 ·2H2 O, five univariant solubility curves and two invariant points. Combining Pitzer binary parameters obtained in the literatures, the Pitzer mixing parameters θ Na, Ca, θ Na, Sr, θ Ca, Sr, Ψ Na, Ca, Cl, Ψ Na, Sr, Cl and Ψ Ca, Sr, Cl were fitted with the solubility data in this study and literatures. The model was then used for predicting the solubilities of the two systems. The experimental data are in accordance with the predicted results.